Design, production and immunomodulatory potency of a novel allergen bioparticle - Gomord, Véronique (PLoS One, 2020)
Allergen immunotherapy (AIT) is the only disease-modifying treatment with evidence for sustained efficacy. However, it is poorly developed compared to symptomatic drugs. The main reasons come from treatment duration implying monthly injections during 3 to 5 years or daily sublingual use, and the risk of allergic side-effects. To become a more attractive alternative to lifelong symptomatic drug use, improvements to AIT are needed. Among the most promising new immunotherapy strategies is the use of bioparticles for the presentation of target antigen to the immune system as they can elicit strong T cell and B cell immune responses. Virus-like particles (VLPs) are a specific class of bioparticles in which the structural and immunogenic constituents are from viral origin. However, VLPs are ill-suited for use in AIT as their antigenicity is linked to structure. Recently, synthetic biology has been used to produce artificial modular bioparticles, in which supramolecular assemblies are made of elements from heterogeneous biological sources promoting the design and use of in vivo-assembling enveloped bioparticles for viral and non-viral antigens presentation. We have used a coiled-coil hybrid assembly for the design of an enveloped bioparticle (eBP) that present trimers of the Der p 2 allergen at its surface, This bioparticle was produced as recombinant and in vivo assembled eBPs in plant. This allergen biotherapeutic was used to demonstrate i) the capacity of plants to produce synthetic supramolecular allergen bioparticles, and ii) the immunomodulatory potential of naturally-assembled allergen bioparticles. Our results show that allergens exposed on eBPs induced a very strong IgG response consisting predominantly of IgG2a in favor of the TH1 response. Finally, our results demonstrate that rDer p 2 present on the surface of BPs show a very limited potential to stimulate the basophil degranulation of patient allergic to this allergen which is predictive of a high safety potential.